Implementasi Data Mining Dalam Pengelompokan Jurusan yang Diminati Siswa SMK Negeri 1 Lolowa'u menggunakan Metode Clustering - Ndruru, Eferoni; Limbong, Riswan (MEANS (Media Informasi Analisa dan Sistem), 2018)
Education is a very important thing and will continue to grow as time goes by, in Indonesia it is rather difficult to keep up with that development. In an effort to provide quality education in a school institution, it is necessary to attract students in choosing the best department in the school. The purpose of this student's specialization in the selection of majors is very important in supporting the knowledge of higher education and the enthusiasm of these students in developing knowledge in the chosen field, such as problems that have occurred in Lolowa'u N 1 Vocational School where students choose majors in accordance with people's encouragement others without any interest in the department, resulting in a decrease in enthusiasm for learning. Therefore, the grouping of students 'data in each department is done and grouped by value, because from this value can be seen the students' enthusiasm for learning. . Data mining is one way to convert data into useful information and can produce new knowledge. The method used is clustering, this clustering method is a method of grouping data. The results obtained in this study are the results of grouping data based on values and can be determined by interested students.